Is ability grouping an answer to teaching English in large ESL classes in Sri Lanka? - Perera, M.E.S. (My University, 2011)
This paper is based on a collaborative action research. The purpose of the study was to find out strategies to minimize the problems resulting in student heterogeneity in the Sri Lankan second language classrooms. In this research the principal researcher and the two assistant researchers who were University academics Collaborated with five practicing teachers and two Regional English Support Centre (RESC) staff to carry out this collaborative action research. First the activities in the Unit six of the Pupils textbook (Grade 7 and 10) were matched with the Competencies identified in the Teacher Instructional Manual. Later, the activities given were adapted to cater to three different ability levels. Students were grouped into three levels based on their marks obtained at the end of the second term test. In the same class the three different levels of students were taught using the different activities. Even though, at the beginning the majority of the students were not in favour of the same ability grouping, at the end of the intervention majority of the students were happy about it. The teachers, the RESC staff as well as the University staff agree that teaching same ability groups using differentiated tasks were a success. Further, students’ marks at the end of the year tests also show a positive improvement, especially among the less able students. Therefore, the findings of this study indicate that using same ability groups with differential tasks is a possibility in minimizing student heterogeneity which is a serious problem in the large ESL classes in Sri Lanka.

It is believed that one of the main tenant of teacher professional development Courses should be transfer of skills. . However, the literature claims that there is often a gap between what is learnt in the course and what is practiced on the job. Thus there is a need for while theory is derived form practice theory to be also tested in practice. Based on student feed back this paper examines how while Experiential learning can provide a model for the way teachers learn about teaching, the teaching practice cycle provides opportunities to test this knowledge. Feedback over a three year period of Post Graduate Diploma students following a one year teacher Development Course in Sri Lanka reveals that the teaching practicum had been the most useful component in the Course. Further it has helped them to relate the different types of learning involved in experiential learning to the teaching practice cycle. During the last two years an action research was incorporated to the teaching practice cycle. Quantitative data based on questionnaire responses as well as qualitative responses of a sample of students and mentor observations reveal that the incorporation of the action research has enabled the trainees to reflect on their experiences. All participants agreed that such reflections had positive impact on their continuous professional development.